Relationship between intraoperative hypothermia and hyperthermia with postoperative pulmonary infection and surgical site infection in major non-cardiac surgery - Pang, Qian-Yun; Yang, Ya-Jun; Feng, Yu-Mei; Sun, Shu-Fang; Liu, Hong-Liang (Frontiers in Medicine, 2024)
Background: Surgical patients often experience intraoperative hypothermia or hyperthermia, but its relationship with postoperative pneumonia (PPI) and surgical site infection (SSI) is unclear. Here, we conduct a retrospective cohort study to address these issues .Methods: Adult patients undergoing major non-cardiac surgery under general anesthesia were recruited for eligibility. Three indices of core body temperature under hypothermia (<36 0 C) or hyperthermia (>37.3 0 C) were calculated: absolute value ( 0 C), duration of exposure (min), and AUC (area under the curve, 0 C×min). The outcomes were in-hospital PPI and SSI. The risk-adjusted association between intraoperative hypothermia or hyperthermia and PPI or SSI was determined.The absolute value (nadir value of hypothermia or peak value of hyperthermia) was not associated with PPI or SSI. PPI was associated with 1) duration: hypothermia >90 min (OR:1.425, 95%CI:1.131-1.796),